Secondary battery and electric device
By controlling the relative content of fluorine atoms in the interface film of the dry negative electrode sheet, the side reaction problems caused by the increase in the surface area of the active particles and binder of the dry process system battery are solved, and the first effect and cycle life of the battery are improved.
Patent Information
- Application Number
- CN202510156935.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the preparation process, the surface area increase caused by the breakage of active particles of the negative electrode sheet and the fibrosis of the binder can easily induce undesired side reactions, reducing the first Coulomb efficiency and cycle life.
By controlling the relative content of fluorine atoms in the interface film of the active material layer of the dry negative electrode sheet, 85%≤a+b≤100% (where a is the molar content of fluorine atoms in lithium fluoride, b is the molar content of fluorine atoms in lithium fluoride), and the interface film contains 0≤c≤15% carbon-containing fluorine bond substances to inhibit side reactions and the reduction of the binder.
Effectively passivate the negative electrode active material and binder, inhibit undesired side reactions of electrolytes, and improve the first effect and cycle life of the secondary battery.
Smart Images

Figure CN119627035A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a secondary battery and an electrical device. Background Art
[0002] The dry electrode process is a comprehensive upgrade over the traditional wet process, which can bring about a huge improvement in battery performance and cost. In terms of battery performance, dry-process batteries can achieve higher energy density, and the battery's electrical performance and safety performance are both better; in the manufacturing process, dry electrodes have fewer steps, lower manufacturing costs and energy consumption, and the raw materials are environmentally friendly, more suitable for large-scale production, and can bring greater economic benefits. On the application side, dry-process batteries are more suitable for the manufacturing needs of new-generation batteries such as solid-state batteries and large cylindrical batteries.
[0003] However, the current domestic dry electrode technology is not yet fully mature, and there are still many process technical difficulties. The performance of batteries in the dry process system needs to be further improved. Summary of the invention
[0004] The inventors of this application found that, on the one hand, the dry-process negative electrode sheet will undergo multiple rolling processes during the preparation process, resulting in an increase in the breakage of active particles and an increase in the active specific surface area, which is more likely to induce undesirable side reactions in the electrolyte; on the other hand, the specific surface area of polytetrafluoroethylene (PTFE), a binder unique to the dry process, will also increase after fiberization, and PTFE is not resistant to reduction, which is also likely to induce undesirable side reactions in the electrolyte. These side reactions will lead to a decrease in the first coulomb efficiency (first effect) and cycle life of the dry-process system battery. In response to this discovery, the inventors of this application found that by controlling the relative content of fluorine atoms in lithium fluoride, fluorine-containing lithium phosphate, and carbon-fluorine bond-containing substances in the interface film of the active material layer of the dry-process negative electrode sheet, the capacity loss caused by the active particles and the binder surface and the undesirable side reactions of the electrolyte can be suppressed, thereby improving the first effect and cycle performance of the dry-process system battery.
[0005] The first aspect of the present application provides a secondary battery, which includes a positive electrode plate, a negative electrode plate and an electrolyte, wherein the negative electrode plate includes a negative electrode active material layer and a solid electrolyte interface film formed on the surface of the negative electrode active material layer, wherein the solid electrolyte interface film contains lithium fluoride, fluorine-containing lithium phosphate and a substance containing a carbon-fluorine bond, and an X-ray photoelectron spectrometer is used to test after sputtering and etching for 10 minutes. Based on the total amount of fluorine atoms in the solid electrolyte interface film, the molar content of fluorine atoms in the lithium fluoride is a, the molar content of fluorine atoms in the fluorine-containing lithium phosphate is b, and the molar content of fluorine atoms in the substance containing a carbon-fluorine bond is c, wherein 85%≤a+b≤100%, 0≤c≤15%; and the negative electrode active material layer also includes a binder, and the binder includes polytetrafluoroethylene.
[0006] A second aspect of the present application provides an electrical device, wherein the electrical device comprises the secondary battery described in the first aspect.
[0007] The beneficial effects of this application are: The secondary battery of the present application controls the relative content of fluorine atoms in lithium fluoride, fluorine-containing lithium phosphate and carbon-fluorine bond-containing substances in the interface film formed on the surface of the active material layer in the dry-process negative electrode sheet, thereby being able to better passivate the negative electrode active material and the binder, inhibiting undesirable side reactions of the electrolyte while inhibiting the reduction and lithium consumption of the negative electrode binder, thereby improving the initial efficiency and cycle life of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 This is the XPS fluorine spectrum of the interface film of the negative electrode active material layer in the secondary battery of Example 9 of the present application. DETAILED DESCRIPTION
[0009] For simplicity, this application only specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an undefined range; and any lower limit can be combined with other lower limits to form an undefined range, and any upper limit can be combined with any other upper limit to form an undefined range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an undefined range.
[0010] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0011] A list of items connected by the terms "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C.
[0012] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.
[0013] Primary and secondary batteries The secondary battery provided by the present application includes a positive electrode plate, a negative electrode plate and an electrolyte, wherein the negative electrode plate includes a negative electrode active material layer and a solid electrolyte interface film formed on the surface of the negative electrode active material layer, wherein the solid electrolyte interface film contains lithium fluoride, fluorine-containing lithium phosphate and a substance containing a carbon-fluorine bond, and an X-ray photoelectron spectrometer is used to perform a test after sputtering and etching for 10 minutes. Based on the total amount of fluorine atoms in the solid electrolyte interface film, the molar content of fluorine atoms in the lithium fluoride is a, the molar content of fluorine atoms in the fluorine-containing lithium phosphate is b, and the molar content of fluorine atoms in the substance containing a carbon-fluorine bond is c, wherein 85%≤a+b≤100%, 0≤c≤15%; and the negative electrode active material layer also includes a binder, and the binder includes polytetrafluoroethylene.
[0014] The inventors of the present application have discovered through research that by controlling the distribution of fluorine elements in the interface film of the active material layer of the negative electrode sheet and ensuring the chemical stability and mechanical strength of the interface film by appropriately having a higher content of inorganic fluorine (including LiF, LixPFy and LixPOyFz) and a lower content of organic fluorine (i.e., substances containing carbon-fluorine bonds) in the interface film, the negative electrode active materials and binders with increased specific surface area introduced by the dry process can be effectively passivated, and undesirable side reactions of the electrolyte on the surface of the active material layer can be reduced, thereby improving the initial efficiency and cycle of the secondary battery.
[0015] In the present application, the solid electrolyte interface membrane is a non-artificial membrane. In some embodiments, the solid electrolyte interface membrane is obtained by reducing the electrolyte on the surface of the negative electrode active material layer.
[0016] In the present application, the molar content of fluorine atoms in the solid electrolyte interface film refers to the molar content of the atom in the entire solid electrolyte interface film region on the surface of the negative electrode active material, and is the molar content of the atom in the interface film within the entire interface film depth region, rather than the molar content of the atom in the interface film within a portion of the interface film depth region at a distance from the interface side of the interface film and the electrolyte.
[0017] In some embodiments, the negative electrode active material layer does not contain a solvent, specifically does not contain detectable processing solvents, processing solvent residues and processing solvent impurities. These processing solvents include but are not limited to water, pyrrolidone, acetate, ketone, alcohol, glycol, toluene, xylene.
[0018] In some embodiments, a+b is illustratively 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 97%, 99% or any value therebetween. If the value of a+b is too low, the inorganic component in the interface film is less, and the negative electrode active material and binder cannot be effectively passivated, and the undesirable side reactions of the electrolyte such as lithium consumption of the active material and PTFE reduction are suppressed, resulting in a reduction in the first effect and cycle of the battery. At the same time, the mechanical strength and chemical stability of the interface film will also be insufficient, affecting the cycle life of the battery. If the value of a+b is too high, the impedance of the interface is large, which reduces the transmission speed of lithium ions and reduces the cycle life of the battery. In some embodiments, 75%≤a≤95%.
[0019] In some embodiments, 75%≤a≤95%, a is illustratively 75%, 78%, 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 95% or any value therebetween. If the value of a is too low, the content of lithium fluoride in the interface film is relatively small, and it is difficult to effectively suppress the undesirable side reactions such as the reduction and consumption of lithium by chemical materials and PTFE, resulting in a reduction in the first efficiency and cycle of the battery. At the same time, the mechanical strength and chemical stability of the interface film will also be insufficient, affecting the cycle life of the battery. If the value of a is too high, the structure of the interface film is too dense, increasing the resistance of lithium ions and reducing their transmission speed, resulting in a reduction in the cycle life of the battery. In some embodiments, 84%≤a≤95%.
[0020] In some embodiments, 1%≤b≤15%, where b is illustratively 1%, 3%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 15%, or any value therebetween. If the value of b is too low, the mechanical strength and chemical stability of the interface film will also be reduced, resulting in a reduced cycle life of the battery. If the value of b is too high, the ionic conductivity of the interface film will decrease, hindering ion transport and being detrimental to the cycle life of the battery. In some embodiments, 5% <b<15%。
[0021] In some embodiments, c is illustratively 0%, 3%, 5%, 7%, 8%, 10%, 11%, 12%, 15% or any value therebetween. If the value of c is too high, there will be too many side reactions involving the electrolyte solvent, lithium salt and additives, and the initial efficiency and cycle of the battery will be reduced. <c≤10%。
[0022] In some embodiments, 0 ≤ c / a ≤ 0.2, and c / a is exemplarily 0, 0.005, 0.01, 0.03, 0.05, 0.07, 0.09, 0.11, 0.13, 0.15, 0.18, 0.2, or any value therebetween. In some embodiments, 0 < c / a ≤ 0.1. In some preferred embodiments, 5% < b < 15%, and 0.02 ≤ c / a ≤ 0.1.
[0023] In some embodiments, the electrolyte includes an additive, and the reduction potential of the additive relative to Li + / Li is greater than or equal to 0.8V. The additive has a high reduction potential (vs Li). During the first charge-discharge process, the additive will be preferentially reduced first, and an effective passivation film will be formed on the surface of the negative electrode active material layer, inhibiting the reduction of lithium consumption by PTFE, and at the same time reducing the undesired side reactions that occur when the electrolyte contacts the active material layer, thereby improving the initial efficiency and cycle performance of the secondary battery.
[0024] In some embodiments, the additive includes one or more of lithium bis(oxalato)borate, lithium difluoro(oxalato)borate, fluoroethylene carbonate, ethylene carbonate, tetravinylsilane, 1,3-propane sultone, and 1,3-propene sultone. In some embodiments, based on the mass of the electrolyte, the mass content of the additive is 0.2% - 20%. In some embodiments, the additive includes one or more of lithium bis(oxalato)borate, lithium difluoro(oxalato)borate, and fluoroethylene carbonate. In some embodiments, the additive includes lithium bis(oxalato)borate and fluoroethylene carbonate, or lithium difluoro(oxalato)borate and fluoroethylene carbonate. In some embodiments, based on the mass of the electrolyte, the electrolyte includes 0.3% - 2% of lithium bis(oxalato)borate and / or lithium difluoro(oxalato)borate. In some embodiments, based on the mass of the electrolyte, the electrolyte includes 2% - 15% of fluoroethylene carbonate. In some embodiments, based on the mass of the electrolyte, the electrolyte includes 0.3% - 2% of lithium bis(oxalato)borate and / or lithium difluoro(oxalato)borate and 2% - 10% of fluoroethylene carbonate.
[0025] In some embodiments, the additive may further include at least one of succinonitrile, adiponitrile, 1,3,6-hexanetricarbonitrile, tris(trimethylsilyl) phosphate, and lithium difluorophosphate.
[0026] In some embodiments, the electrolyte further comprises a solvent, and the solvent comprises a carboxylate and a carbonate. In some embodiments, the carboxylate comprises a chain carboxylate, and the chain carboxylate is selected from at least one of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone and a fluorocarboxylate. In some embodiments, the carboxylate is methyl acetate. In some embodiments, based on the mass of the solvent, the mass content of the chain carboxylate is 5%-15%, exemplarily 5%, 8%, 10%, 12%, 15% or any value therebetween.
[0027] In some embodiments, the carbonate includes linear carbonate and cyclic carbonate. In some embodiments, the linear carbonate is selected from at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate and ethyl propyl carbonate. In some embodiments, the cyclic carbonate includes at least one of ethylene carbonate, propylene carbonate, butylene carbonate and fluoroethylene carbonate. In some embodiments, the linear carbonate includes dimethyl carbonate and ethyl methyl carbonate, and the cyclic carbonate includes ethylene carbonate. In some embodiments, based on the mass of the solvent, the mass content of the linear carbonate is 50%-80%, exemplarily 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80% or any value therebetween. In some embodiments, based on the mass of the solvent, the mass content of the cyclic carbonate is 5%-15%, exemplarily 5%, 8%, 10%, 12%, 15% or any value therebetween.
[0028] Increasing the ratio of chain carbonate and chain carboxylic acid ester in the electrolyte solvent is beneficial to reducing the viscosity of the electrolyte, improving the wettability of the electrolyte, and helping to further improve the initial efficiency and cycle of the secondary battery.
[0029] In some embodiments, the electrolyte further comprises a lithium salt, and the lithium salt comprises lithium hexafluorophosphate and / or lithium bis(trifluoromethanesulfonyl)imide. In some embodiments, the lithium salt comprises lithium hexafluorophosphate.
[0030] In some embodiments, the solvent includes 5%-15% of methyl acetate, 1%-15% of cyclic ethylene carbonate and / or cyclic propylene carbonate, and 50%-80% of dimethyl carbonate and / or ethyl methyl carbonate, based on the mass of the solvent.
[0031] In some embodiments, based on the mass of the negative electrode active layer, the mass content of polytetrafluoroethylene is d, and 0 < d ≤ 5%. d is exemplarily 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5% or any value therebetween. In some preferred embodiments, 0.5% ≤ d ≤ 3%. The inventors of the present application have found that when PTFE is used as a binder in the negative electrode sheet, the initial efficiency of the battery will be significantly reduced, which is related to the poor reduction stability and irreversible decomposition of PTFE. However, the present invention effectively passivates the negative electrode active material and the binder with an increased specific surface area introduced by the dry process by controlling the distribution of fluorine elements in the interfacial film of the active material layer, inhibits the reduction lithium consumption of PTFE, and thus improves the initial efficiency of the battery.
[0032] In some embodiments, the negative electrode sheet is a dry-process negative electrode sheet. The dry-process negative electrode sheet can be obtained by a conventional dry process in the art.
[0033] In some embodiments, the negative electrode active material includes a carbon-based material and a silicon-based material. The carbon-based material includes at least one of artificial graphite and natural graphite. The silicon-based material includes at least one of silicon oxide and silicon-carbon composite. In some embodiments, based on the mass of the negative electrode active material, the mass content of the silicon-based material is 5% - 30%, exemplarily 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30% or any value therebetween. In some embodiments, based on the mass of the negative electrode active material, the mass content of the silicon-based material is 8% - 15%. As is well known, silicon anodes have always faced the problem of low initial efficiency. The higher the silicon content in the negative electrode active material, the more prominent the initial efficiency problem. The introduction of the dry process will also lead to an increase in the active area of the silicon negative electrode active material, making it easier to increase the consumption of irreversible lithium during the first charge and discharge process, further reducing the initial efficiency. However, the present invention can effectively improve the initial efficiency and cycle performance of the silicon negative electrode secondary battery by controlling the distribution of fluorine elements in the interfacial film of the active material layer.
[0034] In some embodiments, the negative electrode sheet further includes a second binder, and the second binder is selected from one or more of polyvinylidene fluoride, styrene-butadiene rubber, nitrile rubber, sodium carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile, and sodium alginate. In some embodiments, the mass ratio of the polytetrafluoroethylene to the second binder is (0.5 - 5):1. In some embodiments, the negative electrode sheet further includes a conductive agent, and the conductive agent is selected from one or more of conductive carbon black, carbon fiber, graphene, conductive graphite, and carbon nanotubes.
[0035] In some embodiments, based on the mass of the negative electrode active layer, the negative electrode plate includes 70%-90% of carbon-based active material, 5%-30% of silicon-based active material, 0.5%-3% of PTFE, 0.2%-1.5% of the second binder, and 0.5%-5% of the conductive agent.
[0036] In some embodiments, the negative electrode plate is made by a method comprising the following steps: (I) mixing the negative electrode active material and the conductive agent to obtain a mixture A; (II) mixing the mixture A with polytetrafluoroethylene and performing a fiberization treatment to obtain a mixture B; (III) rolling the mixture B into a film to form a self-supporting film; (IV) Composite the self-supporting film with a current collector.
[0037] In some embodiments, the negative electrode active layer further includes the second binder, and the negative electrode plate is prepared by a method comprising the following steps: (I) dry-mixing the negative electrode active material, the second binder and the conductive agent to obtain a mixture A; (II) dry-mixing the mixture A with polytetrafluoroethylene and performing a fiberization treatment to obtain a mixture B; (III) rolling the mixture B into a film to form a self-supporting film; (IV) Composite the self-supporting film with a current collector.
[0038] In some embodiments, in step (I) and step (II), the mixing line speed is 15m / s-40m / s, and the mixing temperature is 20°C-80°C. In some embodiments, in step (III), the roller surface temperature of the rolling is 30°C-130°C, such as 50°C-100°C, and the roller line pressure of the rolling is 0.01t / cm-2t / cm. In some embodiments, in step (IV), the compounding temperature is 100°C-150°C, and the compounding roller line pressure is 0.01t / cm-0.5t / cm.
[0039] In some embodiments, the positive electrode plate includes a positive electrode active material, and the positive electrode active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, and lithium-rich manganese-based materials.
[0040] In some embodiments, the positive electrode active material includes LiNi m Co n A (1-m-n) O 2The lithium nickel transition metal oxide shown, wherein A is selected from at least one of manganese, aluminum, magnesium, zirconium, strontium, yttrium, lanthanum, molybdenum, silver, niobium, iron, titanium, copper, zinc, chromium, calcium, barium and tungsten, 0.5≤m≤1, 0≤n≤0.5, m+n≤1. Wherein, m is exemplarily 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1 or any value therebetween, and n is exemplarily 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5 or any value therebetween. In some embodiments, 0.7≤m≤1, 0≤n≤0.3.
[0041] In some embodiments, the positive electrode sheet further comprises a binder and a conductive material. In some embodiments, the positive electrode sheet is a wet positive electrode sheet, which is prepared by a conventional wet process. In some embodiments, the positive electrode sheet is a dry positive electrode sheet, which is prepared by a dry process.
[0042] In some embodiments, the secondary battery comprises a positive electrode sheet, a dry negative electrode sheet, and an electrolyte. In some embodiments, the secondary battery comprises a wet positive electrode sheet, a dry negative electrode sheet, and an electrolyte. In some embodiments, the secondary battery comprises a dry positive electrode sheet, a dry negative electrode sheet, and an electrolyte.
[0043] In some embodiments, the preparation method of the secondary battery includes providing an electrode assembly, injecting, packaging and forming. In some embodiments, the temperature of the formation is 40°C to 50°C, for example, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C or 49°C. In some embodiments, the pressure of the formation is 450kgf to 550kgf, for example, 460kgf, 470kgf, 480kgf, 490kgf, 500kgf, 510kgf, 520kgf, 530kgf or 540kgf. In some embodiments, the charging current of the formation is 0.05C-0.3C, and the discharge current of the formation is 0.1C-0.5C.
[0044] In some embodiments, the formation comprises: charging to 4.0V at 0.1C current and standing for 10 min, and then discharging to 2.5V at 0.2C current under the conditions of temperature of 40°C-50°C, such as 45°C, pressure of 450kgf-550kgf, such as 500kgf.
[0045] In some embodiments, the secondary battery is formed. In some embodiments, the solid electrolyte interface membrane is obtained by the formation of the secondary battery. During the formation process of the secondary battery, the electrolyte is reduced to form a film on the surface of the negative electrode active material layer, inhibiting the reduction of PTFE and the continuous reaction of the electrolyte on the surface of the active material layer. After the secondary battery has been cycled many times, the absolute content of the amount of fluorine atoms from lithium fluoride, fluorine atoms from fluorine-containing lithium phosphate, and fluorine atoms from carbon-fluorine bond-containing substances in the interface membrane will be slightly different from the absolute content after formation, but the relative content still meets 85%≤a+b≤100%, 0≤c≤15%.
[0046] In some embodiments, the secondary battery may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc.; or a soft package, such as a bag-type soft package, and the material of the soft package is non-limitingly polypropylene, polybutylene terephthalate, and polybutylene succinate. In the present application, there is no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.
[0047] In some embodiments, the present application further provides a battery module. The battery module includes the above-mentioned secondary battery. The battery module of the present application uses the above-mentioned secondary battery, and therefore has at least the same advantages as the secondary battery. The number of secondary batteries contained in the battery module of the present application can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0048] In some embodiments, the present application further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0049] 2. Device The present application also provides a device, which includes at least one of the above-mentioned secondary battery, battery module or battery pack.
[0050] In some embodiments, the device includes, but is not limited to: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. In order to meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or battery module may be used.
[0051] In other embodiments, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a secondary battery may be used as a power source. Examples and Comparative Examples
[0052] In this application, unless otherwise specified, all materials or reagents used are commercially available. Example 1
[0053] Preparation of electrolyte: In a nitrogen-protected glove box (water content <1ppm, oxygen content <1ppm), 10wt% of ethylene carbonate, 55wt% of dimethyl carbonate, 9wt% of ethyl methyl carbonate, 11wt% of methyl acetate and 15wt% of lithium hexafluorophosphate were mixed uniformly to prepare a basic electrolyte, and then 0.5wt% of lithium borate was added to the basic electrolyte and stirred uniformly to obtain the electrolyte of Example 1.
[0054] Preparation of negative electrode sheet: Active material (graphite and silicon-carbon composite weight ratio 90:10) and conductive agent carbon black are mixed at a weight ratio of 96:1.5, and mechanically stirred for 3~5min to obtain mixture M1; a second binder sodium carboxymethyl cellulose (CMC-Na) particles are added to the mixture M1, and mechanically stirred for 3~5min to obtain a mixture M2, wherein the weight ratio of the second binder to the conductive agent is 0.5:1.5; a first binder polytetrafluoroethylene (PTFE) is added to the mixture M2, and mechanically stirred for 3~5min to obtain a fiberized mixture, wherein the weight ratio of the first binder to the conductive agent is 2:1.5. Each mechanical stirring is mixed by high-speed shearing, the shear speed limit is controlled at 40m / s, and the shear temperature is controlled at 20℃-80℃. The fiberized mixture is rolled into a film on a roller machine, the roller surface temperature is set to 70℃, and the roller line pressure is set to 0.4t / cm to form a negative electrode self-supporting film. The obtained self-supporting film was compounded with the current collector, the roller surface temperature was set to 110° C., and the line pressure between the rollers was set to 0.08 t / cm to prepare a negative electrode sheet.
[0055] Preparation of positive electrode: Mix the binder polyvinylidene fluoride (PVDF) with water, stir to obtain glue, and then add the active material LiNi 0.8 Co 0.1 Mn 0.1 O 2 Add carbon black and conductive agent into the glue, mix and stir to obtain positive electrode slurry, wherein the weight ratio of active material, binder and conductive agent is 96:1.5:2.5; evenly spread the positive electrode slurry on aluminum foil, and obtain positive electrode sheets after baking, rolling and cutting.
[0056] Diaphragm: Polyethylene ceramic coated composite diaphragm is selected.
[0057] Preparation of lithium-ion battery: stack the prepared positive electrode sheet, separator and negative electrode sheet in order, make the separator in the middle of the positive and negative electrode sheets, and wind them to obtain a bare battery cell; place the bare battery cell in an aluminum-plastic film outer package, inject the prepared electrolyte after sufficient drying, wherein the electrolyte injection volume is 8.2g; the battery is placed at 45°C for 48h, and formed in a high-temperature fixture (the formation conditions are: temperature 45°C, pressure 500kgf, 0.1C current charging to 4.0V and then placing for 10 min, then 0.2C discharge to 2.5V, then evacuate and seal, and divide the capacity (0.33C charge and discharge twice) to obtain a lithium-ion battery. Examples 2-15 and Comparative Example 1
[0058] Examples 2 to 15 and Comparative Example 1 are achieved by adjusting the type and content of electrolyte additives, the content of the first binder PTFE and the formation conditions on the basis of Example 1. The specific adjustment measures and detailed data are shown in Table 1. The sum of the mass content of PTFE and active material in each example and comparative example is 98%, and the content of the second binder and the conductive agent are the same.
[0059] Table 1 Test Method
[0060] 1. Determination of interfacial film composition The lithium-ion batteries of each embodiment and comparative example were discharged at a constant current of 0.1C to 2.5V, and then the batteries were disassembled in a glove box filled with argon to obtain negative electrode sheets. The obtained negative electrode sheets were cut into test samples of 4mm×4mm in size, and soaked in a low-boiling dimethyl carbonate DMC solvent for 10min, then rinsed 3 times, and then placed for 5h. After the samples were completely dried, they were vacuum transferred to the test chamber of an X-ray photoelectron spectrometer (XPS), with the active layer of the samples facing upward, and the composition of the solid electrolyte interface film on the surface of the active layer was measured and analyzed.
[0061] The specific test conditions and steps are as follows: Using single crystal spectrum AlKα rays, a full spectrum scan was performed in the energy range of 0-1100eV to preliminarily determine the chemical composition of the active layer interface film; then a fine spectrum was scanned in the energy range of 680eV-700eV, and the data when the sputtering etching time was 10 minutes was selected to obtain the F spectrum; then Multipak software was used to calibrate the spectrum peaks and split the peaks, and the calibration used the peak at 284.8eV of neutral carbon C1s as the reference peak for calibration, and according to the energy benchmark XPS standard card, the peaks were separated to obtain the molar percentages of LiF, LixPOyFz&LixPFy and substances containing CF bonds.
[0062] 2. First-effect test During the test, the lithium-ion battery was first charged to 4.25V at 0.33C constant current and constant voltage at 25°C, left to stand for 5 minutes, and then discharged to 2.5V at 0.33C constant current and left to stand for 5 minutes. The battery's first coulombic efficiency (first efficiency) = first discharge capacity / first charge specific capacity) × 100%.
[0063] 3. Cycle test In a 45°C environment, charge the lithium-ion battery to 4.25V at 1C constant current and constant voltage, let it rest for 5 minutes, then discharge it to 2.5V at 1C constant current, let it rest for 30 minutes, and repeat the charge and discharge process until the battery's capacity retention rate decays to 80%, and record the number of battery cycles. Test Results
[0064] Table 2
[0065] By comparing Examples 1-11 and Comparative Example 1, it can be found that the addition of the early film-forming additives will significantly increase the content of inorganic fluorine, especially lithium fluoride, in the interface film and significantly reduce the content of organic fluorine, thereby improving the first effect and cycle of the battery. By comparing Examples 1-5 and Comparative Example 1, it can be found that the addition of boron-containing compounds reduces the content of substances containing carbon-fluorine bonds in the interface film, indicating that the corresponding by-products from solvents and lithium salts are reduced, that is, the side reactions of solvents and lithium salts are reduced, that is, the addition of lithium borate effectively inhibits the generation of solvent and lithium salt side reactions, and the corresponding first effect and cycle are significantly improved.
[0066] Comparing Examples 1-3, it can be found that as the content of LiBOB increases, the content of LiF in the interface film gradually increases, and the content of LixPOyFz & LixPFy inorganic lithium salts and organic lithium salts containing CF bonds gradually decreases. This is because LiBOB is reduced in advance at around 2.2V, and the reduction product is rich in inorganic lithium salts such as LiF, which can be uniformly deposited on the interface of the active material to inhibit the further occurrence of side reactions, and at the same time, the exposed surface of the binder is reduced, reducing its reduction lithium consumption. However, when the content of LiBOB is high, the content of inorganic lithium salts is too high, which will increase the impedance, cause polarization capacity loss during the cycle, and thus shorten the cycle life of the battery.
[0067] By comparing Examples 4 and 5, it can be found that LiDFOB is also beneficial to increase the content of inorganic components in the interface film and improve the first efficiency and cycle of the battery, but its improvement is not as great as that of LiBOB.
[0068] By comparing Examples 6-8, it can be found that as the FEC content increases, the total amount of LiF and inorganic lithium salt in the interface film increases, the content of organic fluorine components gradually decreases, and the first efficiency and cycle of the battery also improve. This is because FEC is reduced at around 1V, and the product is rich in LiF, which can inhibit the lithium-consuming side reaction of the solvent.
[0069] However, considering that a high FEC content will increase the risk of deterioration of storage performance, LiBOB and FEC are used in combination here, namely Example 9. It can be found that the LiF content in its interface film is relatively high, while the organic fluorine component is relatively low, indicating that the composite film formed by the combination of the two additives has strong mechanical and chemical stability, can be more evenly covered on the surface of the active material of the electrode, and can also effectively passivate the binder, so the first effect and cycle are also significantly improved.
[0070] By comparing Examples 9-11, it can be found that with the increase of the binder PTFE, the organic fluorine component in the interface film gradually increases, and the corresponding LiF and fluorine-containing lithium salt content gradually decreases. This is because the PTFE fiberization increases its surface area during the film formation process. The greater the content, the greater the probability of being exposed on the surface of the pole piece. When its content is low (Example 10), the film formation effect of the pole piece is slightly poor, which will make the lithium capacity of the active material in the cycle process insufficient. When its content is high (Example 11), the PTFE fiber itself will consume a certain amount of lithium capacity, which will reduce the first effect and cycle. At the same time, the high content of PTFE will increase the membrane impedance of the pole piece, resulting in a large loss of polarization capacity.
[0071] By comparing Examples 9 and 12-13, it can be found that the appropriate temperature is conducive to achieving better first effect and cycle performance. When the temperature is too low (Example 12), the electrochemical reaction rate on the electrode surface during charging is slow, and the formation consumes less lithium. However, due to its insufficient reaction, the content of inorganic fluorine-containing components in the interface film is also low, the film formation is insufficient, and the film stability is poor, so its cycle life is short. When the temperature is too high (Example 13), the formation charging reaction speed is fast, the content of inorganic fluorine-containing components in the interface film is high, and the corresponding lithium consumption will also increase, so its first effect will be low. Due to the fast reaction speed, the mechanical stability of the membrane components will be reduced, and its cycle will also be reduced.
[0072] By comparing Examples 9 and 14-15, it can be found that a suitable charging rate is conducive to achieving better first-time efficiency and cycle performance. This is because when the charging rate is low (Example 14), the reaction time in the formation charging stage is long, more electrochemical reactions will occur, the content of each element in the interface film is also high, the consumption of lithium capacity increases, the first-time efficiency will be low, and since the formed interface film is denser, the interface film impedance will also increase, resulting in an increase in polarization capacity loss during the cycle. When the charging rate is high (Example 15), the formation interface reaction is faster and shorter in duration, the content of each element in the interface film is also low, the film formation is insufficient and the interface film will be loose, and the first-time efficiency and cycle will also be slightly worse.
[0073] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the scope of the present application as described in the appended claims.
Claims
1. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet, and an electrolyte, characterized in that, the negative electrode sheet includes a negative electrode active material layer and a solid electrolyte interface film formed on the surface of the negative electrode active material layer. The solid electrolyte interface film contains lithium fluoride, lithium fluorophosphate, and a substance containing a carbon-fluorine bond. After 10 minutes of sputter etching time, it is tested using an X-ray photoelectron spectrometer. Based on the total amount of substance of fluorine atoms in the solid electrolyte interface film, the molar content of fluorine atoms in the lithium fluoride is a, the molar content of fluorine atoms in the lithium fluorophosphate is b, and the molar content of fluorine atoms in the substance containing a carbon-fluorine bond is c. Among them, 85% ≤ a + b ≤ 100%, 0 ≤ c ≤ 15%; and, the negative electrode active material layer further includes a binder, and the binder includes polytetrafluoroethylene.
2. The secondary battery according to claim 1, characterized in that: 75% ≤ a ≤ 95%, 1% ≤ b ≤ 15%.
3. The secondary battery according to claim 1 or 2, characterized in that: The electrolyte includes an additive, the additive relative to Li + / The reduction potential of Li is greater than or equal to 0.8V.
4. The secondary battery according to claim 3, characterized in that: The additive includes one or more of lithium bis(oxalato)borate, lithium difluoro(oxalato)borate, fluoroethylene carbonate, ethylene carbonate, tetravinylsilane, 1,3 - propane sultone, and 1,3 - propene sultone.
5. The secondary battery according to claim 4, characterized in that: The additive includes lithium bis(oxalato)borate and fluoroethylene carbonate.
6. The secondary battery according to claim 1 or 2, characterized in that: 0 ≤ c / a ≤ 0.
2.
7. The secondary battery according to claim 1 or 2, characterized in that: 5% < b < 15%, and 0.02 ≤ c / a ≤ 0.
1.
8. The secondary battery according to claim 1 or 2, characterized in that: The secondary battery satisfies at least one of the following conditions: (a) The electrolyte includes a solvent, and the solvent includes a carboxylic acid ester and a carbonate ester; the carboxylic acid ester is selected from at least one of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ - butyrolactone, and fluorinated carboxylic acid ester; the carbonate ester includes a linear carbonate ester and a cyclic carbonate ester. The linear carbonate ester is selected from at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, and ethyl propyl carbonate, and the cyclic carbonate ester is selected from at least one of ethylene carbonate, propylene carbonate, butylene carbonate, and fluoroethylene carbonate; (b) The negative electrode active material includes a carbon-based material and a silicon-based material. The carbon-based material includes graphite, and the silicon-based material includes at least one of silicon oxide and silicon-carbon composite; (c) Based on the mass of the negative electrode active material layer, the mass content of polytetrafluoroethylene is d, and 0 < d ≤ 5%; (d) The positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes a LiNi m Co n A (1-m-n) A lithium nickel transition metal oxide represented by O2, wherein A is selected from at least one of manganese, aluminum, magnesium, zirconium, strontium, yttrium, lanthanum, molybdenum, silver, niobium, iron, titanium, copper, zinc, chromium, calcium, barium and tungsten, 0.5≤m≤1, 0≤n≤0.5, m+n≤1; (e) The solid electrolyte interface film is obtained by reducing the electrolyte on the surface of the negative electrode active material layer.
9. The secondary battery according to claim 8, characterized in that, (a) Based on the mass of the solvent, the mass content of the carboxylic acid ester is 5% - 15%, the mass content of the linear carbonate ester is 50% - 80%, and the mass content of the cyclic carbonate ester is 1% - 15%; (b) Based on the mass of the negative electrode active material, the mass content of the silicon-based material is 5% - 30%; (c) The mass content d of the polytetrafluoroethylene satisfies 0.5% ≤ d ≤ 3%; (d) In the chemical formula of the lithium nickel transition metal oxide, 0.7 ≤ m ≤ 1, 0 ≤ n ≤ 0.
3.
10. An electrical device, which includes the secondary battery according to any one of claims 1 - 9.
Citation Information
Patent Citations
Secondary battery and device
CN116314595A
Wide-temperature type non-aqueous electrolyte, lithium ion battery, battery module, battery pack and electric device
CN116826175A
Electrochemical device and electronic apparatus
CN118248945A
Lithium secondary battery with improved elecrochemical property by dry process and electrolyte additive content control and manufacturing method thereof
KR102636223B1
Cited By
Battery and manufacturing method therefor, and electric device
WO2026194501A1